Bio-Evaluation of 99mTc-Labeled Homodimeric Chalcone Derivative as Amyloid-β-Targeting Probe - Mann, Garima; Chauhan, Kanchan; Kumar, Vikas; Daksh, Shivani; Kumar, Nikhil; Thirumal, M.; Datta, Anupama (Frontiers in Medicine, 2022)
Chalcone derivatives have been successfully utilized for a range of biological applications and can cross the blood-brain barrier easily. β amyloid specific bis chalcone derivative , 6,9-bis(carboxymethyl)-14-(4-((E)-3-(4-(dimethylamino)phenyl)acryloyl)phenoxy)-3-(2-((2-(4-((E)-3-(4-(dimethylamino)phenyl)acryloyl)phenoxy)ethyl)amino)-2-oxoethyl)-11-oxo-3,6,9,12-tetraazatetradecanoic acid, DT(Ch)2 was analysed using molecular modelling to explain the binding modes of the ligand with amyloid fibril and monomer followed by 99mTc-complextion in 95% yield and 98.7% efficiency. High binding specificity of the radiocomplex was established following in vitro evaluation against 100-fold excess of DT(Ch)2. 99mTc-DT(Ch)2 exhibited <3% trans-complexation in human serum after 24 h indicating high stability. Fast clearance rate in pharmacokinetics studies displayed a biphasic pattern with t1/2(F) = 30 min ± 0.09; t1/2(S) = 4 h 20 min ± 0.06. In vivo SPECT imaging in rabbits reiterated pharmacokinetics data with initially high brain uptake followed by rapid washout. Biodistribution studies confirmed initial brain uptake as 1.16 ± 0.02% ID/g after 2 min and brain2min/brain30min ratio was 3.74, comparable to the reported Pittsburgh compound. Radioactivity distribution in the brain was >40% in the cingulate cortex followed by >25% in the hippocampus, a distribution pattern aligned to Alzheimer's affected brain. Radiocomplex also displayed rapid plasma clearance followed by hepatobolic and renal modes of excretion.